STUDI LAJU EROSI DAN INDEKS BAHAYA EROSI (IBE) di SUB DAS CILIWUNG HULU - Andri Noor Ardiansyah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
The occurrence of floods in the Hiilir Ciliwung watershed that hit the area of DKI and surrounding areas was triggered by the higher rate of erosion that occurred in one of the Upper Sub Hulu Ciliwung, namely Sub Ciliwung Hulu. Flood control can be done by using the approach of erosion scale, in Ciliwung Hulu Basin. The sampling technique used in this research is purposive sampling technique that is observation and sampling of soil based on the researcher's consideration of soil condition (K), length and slope (LS) and land use and conservation technique (CP) Then the data is processed using the Soil Loss Equation (USLE) equation The rate of erosion and grade is found in the following plots: one plot of 520.10 ton / ha / yr (very high), plot two 1005.84 ton / ha / yr (very high ), plot three 7.18 ton / ha / yr (very low), plot four 11.39 ton / ha / yr (very low), and plot five 198,13 ton / ha / yr (high) For Erosion Hazard Index (IBE ) are in plot one 21.67 (very high), plot two 45.75 (very high), plot three 0.29 (low), plot four 0.49 (low), and plot five 7.74 (high)